2023
DOI: 10.1007/s42995-023-00165-2
|View full text |Cite
|
Sign up to set email alerts
|

Population structure and genome-wide evolutionary signatures reveal putative climate-driven habitat change and local adaptation in the large yellow croaker

Abstract: The large yellow croaker (Larimichthyscrocea) is one of the most economically valuable marine fish in China and is a notable species in ecological studies owing to a serious collapse of wild germplasm in the past few decades. The stock division and species distribution, which have important implications for ecological protection, germplasm recovery, and fishery resource management, have been debated since the 1960s. However, it is still uncertain even how many stocks exist in this species. To address this, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 87 publications
0
1
0
Order By: Relevance
“…Israeli Journal of Aquaculture -Bamidgeh 24 The foundation of the comparative difference analysis method is a one-way analysis of variance, which compares three or more categorical groups to see if there are differences between them. 14 This study showed the three wild populations' OL/BL、BL/BH, and CPH/CPL ratios were significant.…”
Section: Discussionmentioning
confidence: 99%
“…Israeli Journal of Aquaculture -Bamidgeh 24 The foundation of the comparative difference analysis method is a one-way analysis of variance, which compares three or more categorical groups to see if there are differences between them. 14 This study showed the three wild populations' OL/BL、BL/BH, and CPH/CPL ratios were significant.…”
Section: Discussionmentioning
confidence: 99%